Gambaran Efek Samping Obat Kemoterapi Pada Pasien Kanker Payudara Di RSUD Arifin Achmad Pekanbaru - Suci Rahma Ningsih; Wahyu Margi Sidoretno (Jurnal Ilmu Kesehatan Abdurrab, 2024)
The most prevalent cancer in women, though it can strike men as well, is breast cancer. Breast cancer is brought on by unchecked cell proliferation, which, if uncontrolled, can turn into a malignant tumour. One breast cancer treatment that requires monitoring and careful attention to adverse effects is chemotherapy. Determining the adverse effects of chemotherapy on patients with breast cancer was the goal of this study. This study uses an observational, non-experimental research design that is descriptive and evaluative in nature. Data has been collected from the medical records of 16 patients with 11 chemotherapy medication regimens who satisfied the inclusion criteria and had an initial diagnosis of breast cancer in the July 2023. The seven types of chemotherapy medications that are employed are: paclitaxel, cisplatin, doxorubicin, docetaxel, carboplatin, cyclophosphamide, herzemab, and fonkopec. Docetaxel with carboplatin was the most often prescribed chemotherapeutic medication combination, accounting for 4 individuals (25%). Potential side effects that arise during treatment are mucositis, decreased appetite, nausea and vomiting, alopecia, changes in skin and nail color, myalgia, fatigue, dizziness, weakness and numbness in the legs. The side effects that consistently manifested in all patients (100%) were myalgia, alopecia, and nausea and vomiting, according to the results.